(untitled) (Research, Society and Development, 2020)
This article discusses the following theme Fairy tales: contributions to the process of literacy and literacy. In this sense, we intend to analyze the contributions that the reading of fairy tales brings in the development of reading and writing skills, as well as the perception and oral expression. This study also aimed to reflect on the essential elements that make up the narrative structure of fairy tales, as well as to present the challenges of the teacher in the development of reading fairytales in the classroom. As theoretical support, we used the productions of Bettelheim (2007), Coelho (2008), Josualdo (1993) and others that served as subsidies with their pertinent reflections for the development of a renewed and creative reading practice that enchants the child to the universe. from fairy tales. Fairy tales have been serving as a pedagogical resource for instruction and playfulness throughout the ages. Reading fairy tales contributes to the child’s cognitive and linguistic development. Living with technology does not reduce the enchantment of the read tales, but still teaches through the magical, symbolic, transforming facts and feelings along the path of art.